Inclusion of Ultra-Orthodox Students in Higher Education: A Case Study about Women Seminary in the Engineering College of Jerusalem - Michael Naor; Gavriel David Pinto; Pini Davidov; Julie Benaroch; Adit Kivel (MDPI AG, 2022)
This study examines how far the establishment of an ultra-orthodox (Haredi) women-only curriculum and learning environment crafted for their needs, such as supplementary Biblical studies, fosters students' enrollment and achievement in STEM. The methodology utilizes interviews with administrators accompanied by a Google questionnaire surveying students in order to compare the secular Azrieli College of Engineering with its new ultra-orthodox branch, Tmura Seminary, which aims to promote the acquisition by ultra-orthodox Jewish women of an engineering diploma so that they can find employment in the job market. This objective is significant because the ultra-orthodox community in Israel represents a unique family setting in which the men devote most of their workday to Judaic studies while the women are the breadwinners. The findings of the current study show that addressing the higher education gender gap by purposeful efforts to include ultra-orthodox women is indeed feasible. Still, it remains a challenging endeavor because besides being first-generation students subject to religious constraints, Haredi students are insufficiently prepared in mathematics and English before arriving at the campus, which requires that they participate in an intensive pre-academic preparatory program. The analysis of results showed differences between ultra-orthodox and secular students in their motivation for study, sources of information about suitable education institutions, balancing work and family life priorities, financial need for scholarships, and career path, which is directed toward finding a job in the high-tech industry rather than continuing after graduation to pursue a Master-level degree.